DOI: 10.11606/t.17.2009.tde-23042009-131422
|View full text |Cite
|
Sign up to set email alerts
|

Detecção de risco para problemas no desenvolvimento de bebês nascidos pré-termo no primeiro ano

Abstract: Several biological and environmental risk factors influence the development of preterm infants. The objective of this study was to assess risk factors for development delay in preterm infants born with low birth weight, focusing on the following domains: neurobehavioral achievements in the neonatal phase, as well as personal-social, language and motor developments in the first 8 months of postnatal age. We also aimed to: identify the better predictive model for development, based on the biological and socioeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
15

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 81 publications
0
1
1
15
Order By: Relevance
“…On the other hand, differing from the present study, several authors have found an association between gestational age 31,32 or birthweight 31,32 or a longer stay in the hospital after birth 31 and risk factors for delayed motor development. This difference, in comparison to our results, could be explained by the use of different criteria to determine associations.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, differing from the present study, several authors have found an association between gestational age 31,32 or birthweight 31,32 or a longer stay in the hospital after birth 31 and risk factors for delayed motor development. This difference, in comparison to our results, could be explained by the use of different criteria to determine associations.…”
Section: Discussioncontrasting
confidence: 99%
“…El concepto de RN de riesgo neurológico nació en Inglaterra en 1960, siendo definido, como aquel niño que por sus antecedentes pre, peri o postnatales, tiene más probabilidades de presentar, problemas en el desarrollo, ya sean cognitivos, motores, sensoriales o de comportamiento, pudiendo ser transitorios o definitivos [17]. Barbosa et al [118], Oreiro [119] y Formiga et al [120] consideran que mismo teniendo condiciones esenciales para un buen desarrollo, donde se haya minimizado factores causantes de una morbilidad neonatal leve, los RNMBPN y RNEBPN presentan un desarrollo neurosensoriomotor inferior en comparación a los niños nacidos a término.…”
Section: La Prematuridad Como Factor De Riesgo Para El Desarrollo Motorunclassified
“…Silveira et al [202], verificaron que un 25% de los recién nacidos con [220] defienden que retrasar el momento de la intervención hasta que las anormalidades neuromotoras sean evidentes, hace que el proceso de rehabilitación sea menos efectivo y con mayor coste emocional para la familia En algunos estudios del desarrollo de niños prematuros se ha observado que el desarrollo motor grosero es considerado el más retrasado dentro de otras áreas analizadas [221]. Formiga [120], en su estudio referente a la evaluación motora de niños prematuros, verificó que un 48% de sus niños presentaron retraso motor entre los 2 y 4 meses de edad, un 47% presentaron retraso motor entre los 4 y 6 meses y un 36% de sus niños presentaron retraso motor entre los 6 y 8 meses (siempre considerando ECORR, en casos de evaluaciones realizadas en niños prematuros). En un estudio de Campbell et al [48], que utilizaron la AIMS para determinar retraso motor, encontraron un 28% de la muestra con retraso a los 6 meses de edad.…”
Section: Análisis De Fiabilidadunclassified
See 2 more Smart Citations